(untitled) - Bronson, Mary H (New York, NY, 2005)
This book provides an overview of the health of Australian teenagers and examines many of the issues which affect their developing health and wellbeing. What are the specific issues and concerns of teenage boys and girls, and what is the role of parents, doctors and teachers in encouraging teenagers to make healthy life choices?--Publisher's website
Keywords: Health education (Secondary),Health,Sức khỏe,Sức khỏe học đường; Study and teaching (Secondary),Dạy và học (trung học)